ON THE ISSUE OF DETERMINING THE PRODUCTION COST OF THE CAPITAL RENEWAL OF PASSENGER CARS - Trufanova, A. (Municipal economy of cities. Series: «Economy science», 2024)
In recent years, the inventory of passenger cars has decreased significantly due to the exclusion from service of the ones that have already exhausted their service life. The wear and tear of the passenger rolling stock of Ukrzaliznytsia JSC is approaching 90%. Repair and maintenance costs for outdated railcars account for over half of the industry’s expenses. In conditions of an acute shortage of newly built cars, practically the only way to maintain the operability of the car fleet is to overhaul passenger cars that have exhausted their service life. At the same time, based on the results of operations in different regions, the railway cars have different technical conditions. Also, different car repair enterprises use differing methods for calculating the cost of repairs. It leads to a significant scatter of calculation results. The article is devoted to the issue of creating a generalised methodological approach to determining the production cost of passenger cars overhaul. We have classified production costs and determined which expenses relate to the direct costs of car repair production, the auxiliary production costs, and general production costs. Next, we formulated the components of each of these groups. The article considers the main aspects influencing the formation of costs, particularly labour costs and social contributions, material costs, fuel, electricity, repairs, and equipment depreciation. It also takes into account the cost of return expenses. The proposed scientific approach allows accounting for the actual service life and level of wear of the passenger car, its type, and design features. We carried out an analysis of the factors affecting the production cost of repairing passenger cars. It makes it possible to determine rational technical and organisational solutions to reduce the cost of overhauling passenger cars that have exhausted their service life. The stated provisions have a practical orientation and can be used at the car repair enterprises of the Passenger Company branch of JSC Ukrzaliznytsia.